Knowledge and attitude regarding epidural analgesia among expectant mothers - Thakur, Manisha; Sagar, Nidhi; Tandon, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pain relief is an important issue for women in labour. Epidural analgesia provides safe and effective pain relief. But It has not been fully accepted and is not routinely practiced in most of the centres in developing countries despite of many advantages of this technique. Therefore, this study has been conducted with an objective to assess the knowledge and attitude regarding epidural analgesia among expectant mothers. Methods: A descriptive study was conducted on 60 expectant mothers visiting antenatal OPD at DMC & Hospital, Ludhiana selected by convenience sampling technique. Knowledge assessed by using a structured questionnaire and attitude assessed by 3 point likert scale regarding epidural analgesia. Analysis was done using both descriptive and inferential statistics. Results: The findings of the study revealed that 46.7% expectant mothers had below average level of knowledge, 35% had average level of knowledge and 18.3% had good level of knowledge. 96.7 % had positive attitude and only 3.3 % had negative attitude towards epidural analgesia. Correlation between knowledge with attitude was to be significant (r=0.609; p=0.000). Conclusions: Thus, the study concluded that most of women had below average level of knowledge and but they showed positive attitude regarding epidural analgesia.